PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DENGAN GROUP INVESTIGATION TERHADAP HASIL CHEST PASS BOLABASKET (PADA SISWA KELAS VII SMP NEGERI 2 TEKUNG LUMAJANG) - ABDILLAH, ASVIE (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract One factor that can affect an individual's learning outcomes, the ability of teachers to manage learning by applying the right model and make it easy for students to learn the course material, resulting in better learning. Application of the learning model is wrong or not good to make such errors will continue and if not corrected will still be learning the wrong so dangerous for students and will exacerbate the world of education. In accordance with the definition above, a matter that must be performed by a physical education teacher cooperative learning group type investigation began with the division of the group. Furthermore teachers and their students choose a particular matter with the problems that can be developed from the topics. After the subject agreed with the problem, learners and teachers to determine the research methods developed to solve the problem is a learning model that is currently widely used to make learning student-centered teaching (student oriented), mainly to overcome the problems, especially basketball. The purpose of this study were (1) To determine the effect of the application of learning models Investigation Group to study the basketball chest pass to junior high school students N 2 Tekung Lumajang. (2) To find out how much influence the application of learning models Investigation Group of the basketball chest pass to junior high school students N 2 Tekung Lumajang. Objectives of this study is a class VII student SMP II Tekung and number of samples taken 54 students. In this study researchers used a type of experimental research. The results obtained no effect of the use of learning models Investigation Group of the basketball chest pass in grade VII Junior High School II Tekung the t count > t table 7.653 > 2.056. Learning Group for Investigation of learning outcomes basketball chest pass. At Junior High School students in grade VII II Tekung Lumajang an increase of 5%. It can be said that the effect of the implementation of cooperative learning model of the type of Group Investigation to the learning outcomes basketball chest pass turned out to be an impact on student learning outcomes better. Keywords : learning model, type Cooperative Investigation Group, The learning basketball chest pass.